Distributed energy resources hosting capacity calculation based on PSO algorithm - Li, Yaqiong; Wang, Tongxun; Wang, Zhikai; Wang, Kexin; Yu, Hongyang (SPIE, 2024)
In order to manage integration of Distributed Energy Resources (DER) into the grid, calculation of maximum allowable access capacity of DER is essential. This paper introduced a method of DER hosting capacity calculation based on PSO algorithm. The access capacity in each grid point is set as one element in particle coding chain. Using a testing case study of typical distribution network, the proposed method is conducted. Also, by changing the parameters involved in PSO, the impact of Iteration times, Scale of swarm as well as Calculation times are discussed and compared. Experimental results can prove the convergence and effectiveness of the proposed method.